Modelling consumer behaviour: a comparison between aids and the stone-geary models. (1996)
This work responds to the question: Why are the Almost Ideal Demand System (AIDS) and its quadratic extension, the QUAIDS model better ways ofmodelling consumer behaviour than the StoneGeary' Models? Thus, the work shall deal with proposals of singleequation (or separated equations) and with systems ofequattons where the theory is more striking.  The work starts by defining what is known as consumer behaviour. Secondly, it makes a presentation of the restrictions or properties that demand functions have to possess. Thirdly, tt makes a brief presentation of each model and its main chacterístics, limitations and empirical evidence of using each. In this paragraph, the essay illustrates how can changes in sorne exogenous vanables affect on the consumption ofparticular commodities with especial reference to the way in which different models can allow for the impact ofchanges in income. Finally sorne concluding remarks are made.